Semantics in old portuguese language textbooks adopted in public schools in Florianópolis – SC / Brazil: A preliminary study (Revista Contexto & Educação, 2025)
This study describes and analyzes how semantic contents were approached and discussed in old Portuguese language textbooks for elementary school II, from the end of the 1980s and beginning of the 1990s, which were adopted in public schools in the city of Florianópolis (SC), Brazil. This is a bibliographical and documentary research with a descriptive-analytical nature, with a qualitative and quantitative approach. The partial results indicate that the contents on meaning, which were presented exclusively through fixation exercises on synonyms and antonyms, in the textbooks examined, were treated from the perspective of normative grammar, without fostering critical or reflective sense regarding the uses of expressions and their meaning effects.
Keywords: Teaching and learning; Old Portuguese language textbooks; PNLD; Semantics